Serving Local Seafood As A Superior Strategy For Homestay Tourism In Benan Village, Lingga Regency - Rosie Oktavia Puspita Rini; T Adeliana Susanti; Kartika Cahayani (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
Benan Village in Lingga Regency has extraordinary potential for the abundance of marine resources, but its contribution to tourism competitiveness, especially homestays, has not been optimal due to the limited knowledge of the community in processing techniques and standardization of local culinary presentations. This Community Service (PkM) activity aims to reconstruct the local seafood serving system as a superior strategy in increasing the selling value (value proposition) of homestay tourism in Benan Village. The program implementation method uses a participatory approach through a competency-based training model (Competency-Based Training) which includes situation analysis, authentic Malay menu diversification workshops, and hygienic assistance in modern food plating techniques. The results of the intervention showed a significant improvement in the technical skills (hard skills) and paradigm understanding (soft skills) of homestay management partners related to the standardization of commercial dish aesthetics. The impact of the sustainable potential of this program is linearly able to boost the competitive advantage of local accommodation, which has the potential to extend the length of stay of tourists. Furthermore, the strengthening of the downstream culinary sector creates a broad economic multiplier effect at the site level, ranging from the consistent absorption of traditional fishermen's catches to the empowerment of women's groups as the main actors driving the coastal creative economy. Through this synergy, the traditional culinary identity of Lingga Malay can be preserved adaptively to support the acceleration of sustainable tourism based on community independence in Benan Village.